PERSEPSI SISWA TENTANG LAYANAN INFORMASI KESEHATAN REPRODUKSI REMAJA YANG DIBERIKAN GURU BK SMAN 1 KUBUNG - azhar, silvia kardina (Konselor, 2013)
Abstract The intensity that was lacking in the implementation of information services Adolescent Reproduction Healty (ARH) can build students' negative perceptions of the service information ARH provided by the teacher guidance counseling. The purpose of this study was to describe how students' perceptions about the information services provided ARH by the teacher guidance counseling SMAN 1 Kubung. This study used a descriptive approach. The sampling technique is proportional random sampling. Data was analyzed by persentase technik. The study's findings reveal the overall perceptions of students of SMAN 1 Kubung is well about information services adolescent reproduction healty provided by the teacher guidance counseling. Keyword: perceptions, information services, ARH